2018
DOI: 10.1016/j.marpolbul.2018.02.022
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive large-scale investigation and assessment of trace metal in the coastal sediments of Bohai Sea

Abstract: The Bohai Sea is characterized as a semi-closed sea with limited water exchange ability, which has been regarded as one of the most contaminated regions in China and has attracted public attention over the past decades. In recent years, the rapid industrialization and urbanization around the coastal region has resulted in a severe pollution pressure in the Bohai Sea. Although efforts from official government and scientific experts have been made to protect and restore the marine ecosystem, satisfactory achieve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 56 publications
(21 citation statements)
references
References 37 publications
2
19
0
Order By: Relevance
“…Therefore, the potential risk decreased in the following order: Hgs > Cd > As > Cu > Pb > Cr/Zn. The results were in accordance with previous research, indicating that the sediment pollution of trace metals in the river occurred downstream as far as the adjacent area of the Bohai Sea (Li et al 2018;Zhang et al 2014).…”
Section: Ecological Risks Of Trace Metals In Sedimentssupporting
confidence: 92%
“…Therefore, the potential risk decreased in the following order: Hgs > Cd > As > Cu > Pb > Cr/Zn. The results were in accordance with previous research, indicating that the sediment pollution of trace metals in the river occurred downstream as far as the adjacent area of the Bohai Sea (Li et al 2018;Zhang et al 2014).…”
Section: Ecological Risks Of Trace Metals In Sedimentssupporting
confidence: 92%
“…4. Our observations are in agreement with recent studies which have demonstrated that the differences in land-use largely contribute to changes in pollutant variables in aquatic systems 29,36,40 . Hence, the understanding of anthropogenic pollutions induced by different land-use would provide insights into the management of aquatic resource.…”
Section: Discussionsupporting
confidence: 93%
“…Those observations highlighted the differences in their surrounding land-use. A high level of heavy metal pollution was noted in Jinzhou Bay which was characterized with a high level of Cd, As and Hg pollutions in this investigation, mainly due to wastewater discharge by surrounding mining industries in the past century 36 . The organic pollutant concentrations in marine water columns were found to be generally high for Bohai Bay, with high COD being found in the Bohai Bay sampling stations because of sewage discharge from the big cities (Beijing and Tianjin) 38,39 .…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…Therefore, this species has a great economic value in marine aquaculture (Song et al, 2018). However, metal pollution in the Bohai Sea resulting from industrial discharges has been a concerning issue (Gao et al, 2014;Li et al, 2018a). Unfortunately, there is little information regarding the metal concentrations in the muscle tissues of F. chinensis in the Bohai Sea.…”
mentioning
confidence: 99%